Wolves, Bears, and Their Prey in Alaska : Biological and Social Challenges in Wildlife Management. (National Academies Press, 1997)
This book assesses Alaskan wolf and bear management programs from scientific and economic perspectives. Relevant factors that should be taken into account when evaluating the utility of such programs are identified. The assessment includes a review of current scientific knowledge about the dynamics and management of large mammalian predator-prey relationships and human harvest of wildlife in northern ecosystems, and an evaluation of the extent to which existing research and management data allow prediction of the outcome of wolf management or control programs and grizzly bear management programs. Included is an evaluation of available economic studies and methodologies for estimating the costs and benefits of predator control programs in Alaska.